Sosialisasi dan Edukasi Protokol Kesehatan Bagi Masyarakat Desa - Desmira (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities carried out in Padarincang village are aimed at increasing public knowledge about the importance of maintaining health during the Covid 19 period, in this transitional period, education also changes things that need attention. The final target of this activity is that the community understands the importance of maintaining health and the impact on education during the Covid 19 period, the community becomes more aware of the current education patterns. In the event using google meet media, the event was divided into 2 speaker sessions related to the pattern of discussion about the education period during the Covid period, 19 of whom discussed the socialization of health protocols. In this event the participants who took part were mostly the people around the padarincang area, which was the main objective. This activity was assisted by the KKM 18 UNTIRTA group. The methods used are observation, interview and seminar. The results obtained from this activity are that the community understands the importance of maintaining health during Covid 19 and understands the current government regulations regarding the implementation of education. From the evaluation at the end of the seminar 96% of the activities carried out were successful in accordance with the expected targets and achievements.